Women Entreprenuership among the AO Women In Nagaland: Challenges And Struggles - Longchar, Meyajungla (International Journal of Scientific Research and Management (IJSRM), 2016)
In this article the challenges and the struggles faced by the Ao women in the process of becoming and being an entrepreneur will be discussed. Women entrepreneurship is gaining importance in India in the wake of economic liberalization and globalization. The policy and institutional framework for developing entrepreneurial skills, providing vocation education and training has widened the horizon for economic empowerment of women. By analysing the women entrepreneur’s life and their working patterns, we will be able to access the challenges and the struggles they overcame to become an entrepreneur. The characters that are seen in the women entrepreneurs are commitment, self-belief, risk taking capacity, hard work and perseverance that has contributed in the success of their ventures. The support of the family also plays a great role during the onset of the enterprise. In order to have a better understanding we need to look into the political, social and economic scenario prevailing in Nagaland.  In order to have a better understanding we need to look into the political, social and economic scenario prevailing in Nagaland